Communication Between Traditional Medical Practitioners and Western Medical Professionals - Lampiao, Fanuel; Chisaka, Joseph; Clements, Carol (Frontiers in Sociology, 2019)
The high burden of disease in Malawi is exacerbated by a lack of healthcare professionals, and the inaccessibility of healthcare services to many Malawians, due to geographical and financial barriers. The World Health Organization commends the contribution that traditional and complementary medicine could make to achieve such coverage through its integration into health systems. This study aimed to evaluate the barriers that exist between traditional healers and biomedical practitioners for them to collaborate with each other. In-depth interviews were conducted with traditional healers and biomedical practitioners. Results showed that the two groups were willing to collaborate with each other, but to differing degrees. Traditional healers were more enthusiastic than biomedical practitioners, who had several reservations about traditional healers, and placed certain conditions on prospective collaboration. While traditional healers clearly had confidence in biomedical practitioners’ competencies and respect for their practice, biomedical practitioners lacked trust in traditional healers and would not refer patients to them due to several reservations, such as the lack of scientific basis for traditional medicine. This study points out barriers that affects collaboration between traditional healers and biomedical practitioners and it suggests possible solutions.